Further validation of the Genetic Counseling Self‐Efficacy Scale (GCSES): Its relationship with personality characteristics. Issue 5 (18th December 2019) - Keller, Haley; Wusik, Katie; He, Hua; Yager, Geoffrey; Atzinger, Carrie
Abstract: Demonstrating validity of a tool for genetic counseling self‐efficacy could help determine if this is a useful tool for training outcomes or other purposes in the field. The purpose of the current study was to describe the relationship between genetic counseling self‐efficacy, measured by scores on the Genetic Counseling Self‐Efficacy Scale (GCSES), personality characteristics, clinical characteristics, and performance on the American Board of Genetic Counselors (ABGC) board certification examination. Genetic counselors, recruited via email through the National Society of Genetic Counselors (NSGC) Student Research Survey Program, completed an online questionnaire that included the GCSES, work locus of control (WLOC) scale, trait subscale of the State‐Trait Anxiety Inventory (STAI), and questions related to board examination performance. Higher genetic counseling self‐efficacy factor scores for four of six factors were significantly associated with lower WLOC scores indicative of internal locus of control ( p's < .05); higher genetic counseling self‐efficacy factor scores for all six factors were significantly associated with lower trait anxiety scores ( p's < .05). In addition, increased years of experience and providing direct patient care were found to be significantly related to higher scores for all six‐factor scores on the GCSES ( p's ≤ .05). Multiple linear regression models were performed to assess combined effects of predictor and demographic variables and demonstrated that professional factors were most significantly associated with GCSES factor scores. Findings from the current study provide additional validation for the GCSES and add clarity to the relationships between genetic counseling self‐efficacy, personality characteristics, and professional factors. Validation of the GCSES supports the usefulness of this tool as an outcome for genetic counseling training purposes. In addition, the GCSES could be used for self‐reflective practice for genetic counselors. Further studies are needed to investigate the relationship between genetic counseling self‐efficacy and genetic counselor competency. Abstract :